2020
DOI: 10.1007/s00586-020-06517-1
|View full text |Cite
|
Sign up to set email alerts
|

The short-term impact of COVID-19 pandemic on spine surgeons: a cross-sectional global study

Abstract: Purpose The outbreak of COVID-19 erupted in December 2019 in Wuhan, China. In a few weeks, it progressed rapidly into a global pandemic which resulted in an overwhelming burden on health care systems, medical resources and staff. Spine surgeons as health care providers are no exception. In this study, we try to highlight the impact of the crisis on spine surgeons in terms of knowledge, attitude, practice and socioeconomic burden. Methods This was global, multicentric cross-sectional study on 781 spine surgeons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
(39 reference statements)
3
22
0
Order By: Relevance
“…The questions raised in the letter concerning the study by Khattab et al [1] are important, and we completely agree with the authors.…”
Section: Dear Editorsupporting
confidence: 73%
“…The questions raised in the letter concerning the study by Khattab et al [1] are important, and we completely agree with the authors.…”
Section: Dear Editorsupporting
confidence: 73%
“…Most COVID-19 studies reported on physicians from USA ( n = 23) [ 41 , 52 , 66 , 70 , 77 , 90 – 107 ], China ( n = 22) [ 15 , 49 , 54 56 , 65 , 68 , 73 , 86 , 89 , 102 , 108 118 ] followed by India ( n = 21) [ 40 , 50 , 58 , 63 , 67 , 71 , 102 , 119 – 132 ] [ 41 , 52 , 66 , 70 , 77 ], Italy ( n = 10) [ 32 , 94 , 102 , 125 , 133 138 ], and Turkey ( n = 11) [ 35 , 44 , 94 , 139 – 146 ] [ 28 , 30 , 32 , 34 , 36 , 37 , 42 , 45 , 47 , 48 , 59 , 60 , 62 , 80 , 87 ]. .Sixteen studies reported on physicians from multiple countries [ 47 , 51 , 69 , 94 , 102 , 106 , 125 ,...…”
Section: Resultsmentioning
confidence: 99%
“… Covid-19 pandemic has significant psychological impact on adult Egyptians and it has dramatically affected their social support. 11 The Short-Term Impact of COVID-19 Pandemic on Spine Surgeons: A Cross-Sectional Global Study ( Khattab et al, 2020 ) Healthcare worker (spine surgeons); n = 781; Online survey; Cross-sectional study Knowledge, attitude, practice, PPEs, psychological distress Older age, being an orthopaedic surgeon and working in the private sector was associated with a more significant impact of covid-19. Availability of N95 masks and face masks was associated with lesser psychological distress.…”
Section: Resultsmentioning
confidence: 99%
“…The mental health support for the vulnerable population during this pandemic falls short to meet the needs. Mental health issues of the focussed population patients with Parkinson's disease, spine surgeons have also been studied ( Khattab et al, 2020 ; Shalash et al, 2020 ). These groups of population found to have poor mental health than the general population.…”
Section: Discussionmentioning
confidence: 99%